Kebijakan BMN Hulu Minyak dan Gas Bumi yang Adaptif dalam Mendukung Target Lifting untuk Ketahanan Energi Nasional - Sumartono Sumartono (Mathematics Education Study Program, 2025)
The Indonesian government continues to set oil and gas lifting targets every year. This is done to encourage the upstream oil and gas industry to increase lifting to meet national energy needs and optimize state revenue. However, these targets are often not achieved due to the low level of oil and gas exploration activities in Indonesia. Efforts to improve the business climate for upstream oil and gas activities are always carried out in various sectors, one of which is the management of goods and equipment for upstream oil and gas business activities. These goods and equipment are designated as State-Owned Assets (BMN) managed by the Indonesian government c.q. Ministry of Finance. In this regard, in order to encourage investment interest among investors in the upstream oil and gas sector and to pay attention to the mandate of Law 22 of 2001, it is necessary to carry out good management of upstream oil and gas assets so that it can assist Production Sharing Contractors (KKKS) in managing and providing assets needed in upstream oil and gas business activities. Good management of upstream oil and gas BMN can be carried out through adaptive policies so that it can meet every need and problem faced by KKKS, SKK Migas, and the Indonesian government. This adaptive policy will support the resolution of problems that have not been accommodated in normative regulations so that each legal subject can ensure the completion of its responsibilities in accordance with the provisions of laws and regulations.